Aliran-Aliran Filsafat Pendidikan Islam Dan Implikasinya Terhadap Pendidikan Islam Era Kontemporer - M. Zainal Arifin; Maulana Ishaq Ernas; Abdul Haris; Rosichin Mansur (Journal of Contemporary Islamic Education, 2024)
Islamic education in its journey has experienced a lot of maturation and development until now. This is because it is heavily influenced by the thoughts of figures in implementing the existing learning systems in the educational institutions they develop. The thinking of educational figures is driven by the intersection between the sociocultural realities faced by these figures and the religious thoughts they adhere to, especially Islam. By using literary research methods, this research aims to identify tendencies in Islamic educational philosophy. The aim of this research is to explore the ideological construction of Muslim figures, especially Muslim philosophers, regarding education, because we know that education is the path to human development. The results of this research indicate that the influence of Islamic educational philosophy on the Islamic education model lies in the formation of subjects taught to students. Apart from that, Islamic educational philosophy also helps education find its identity, whether the educational institution adheres to a conservative mindset or a pragmatic and progressive mindset. This study can then also be used as a philosophical basis for every educational practitioner.